PENGARUH LINGKUNGAN KERJA FISIK DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA DINAS TENAGA KERJA PROVINSI SUMATERA UTARA - Lince Febriana; Ferry Panjaitan; Gloria J.M Sianipar; Orlando Steven (LP2M Universitas Bina Bangsa, 2024)
The performance of Civil Servants is often a complaint of various parties, especially the public as recipients of services, slow service, improper attendance of employees at work, disobedience to commuting hours are some of these problems resulting in the general public always assuming that Civil Servants have low performance. Problem formulation: (1) How does the Physical Work Environment affect Employee Performance at the North Sumatra Provincial Manpower Office? (2) How does Work Discipline affect Employee Performance at the North Sumatra Provincial Manpower Office? (3) How does the Physical Work Environment and Work Discipline affect Employee Performance at the North Sumatra Provincial Manpower Office? The purpose of this study is: To determine and analyze the Physical Work Environment and Work Discipline partially and simultaneously on Employee Performance at the North Sumatra Provincial Manpower Office. Data analysis was carried out using the Multiple Liner Regression method using SPSS software version 23. The number of samples in the study was 111 respondents of civil servants at the North Sumatra Provincial Manpower Office. The results of the Physical Work Environment have a positive and insignificant effect on Employee Performance. Work Discipline has a positive and significant effect on performance. Physical Work Environment and Work Discipline simultaneously on the Performance of Employees of the North Sumatra Provincial Manpower Office